Modernization of irrigation system operations - FAO, Bangkok (Thailand)International Water Management, Bangkok (Thailand)Research Centre for Agriculture Environmental Engineering, Bangkok (Thailand)Water and Land Management Institute Maharashtra, Bangkok (Thailand) (Bangkok (Thailand), 1999)
Sumario (En)
Ilus.; 47 ref.
Keywords: RIEGO; SISTEMAS DE RIEGO; MODERNIZACION; INGENIERIA HIDRAULICA; MANEJO DE AGUA